1986
DOI: 10.1083/jcb.103.6.2765
|View full text |Cite
|
Sign up to set email alerts
|

Micromanipulated bivalents can trigger mini-spindle formation in Drosophila melanogaster spermatocyte cytoplasm.

Abstract: Abstract. Single (individual) bivalents in cultured Drosophila melanogaster primary spermatocytes were detached from the spindle with a micromanipulation needle and placed in the cytoplasm. Such bivalents are prevented from rejoining the spindle by a natural membrane barrier that surrounds the spindle, but they quickly orient as if on a spindle of their own and the half-bivalents separate in anaphase. Serial section electron microscopy shows that a mini-spindle forms around the cytoplasmic bivalent, i.e., the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 18 publications
(24 reference statements)
2
29
0
Order By: Relevance
“…Spindle assembly assays using Xenopus egg extracts have demonstrated that chromatin can serve as a template for MT nucleation and stabilisation in vitro [Heald et al, 1996]. Moreover, chromosomes in the meiotic cytoplasm of insect spermatocytes have been shown to stabilize MTs [Church et al, 1986;Zhang and Nicklas, 1995a;Fuge, 1999]. Such observations are compatible with a model of anastral spindle assembly, according to which chromosomes are the source of spindle MTs [Karsenti et al, 1984;Steffen et al, 1986].…”
Section: Centrosome Independent Anastral Spindle Formationmentioning
confidence: 80%
“…Spindle assembly assays using Xenopus egg extracts have demonstrated that chromatin can serve as a template for MT nucleation and stabilisation in vitro [Heald et al, 1996]. Moreover, chromosomes in the meiotic cytoplasm of insect spermatocytes have been shown to stabilize MTs [Church et al, 1986;Zhang and Nicklas, 1995a;Fuge, 1999]. Such observations are compatible with a model of anastral spindle assembly, according to which chromosomes are the source of spindle MTs [Karsenti et al, 1984;Steffen et al, 1986].…”
Section: Centrosome Independent Anastral Spindle Formationmentioning
confidence: 80%
“…It is also consistent with the active role of chromosomes in spindle organisation. For instance, it has been reported that bivalents micromanipulated away from the spindle in Drosophila spermatocytes induce the assembly of anastral minispindles in the cytoplasm (Church et al 1986). Likewise, the removal of chromosomes before NEB has been shown to inhibit spindle assembly in grasshopper spermatocytes (Zhang and Nicklas 1995), although the phenotype of fusolo mutants, recently described, seems to argue otherwise (Bucciarelli et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These experiments indicated that chromatin—even in the absence of a kinetochore—was sufficient to generate a signal that can promote microtubule formation. In parallel, micromanipulation studies in grasshopper spermatocytes revealed that a single chromosome can induce the formation of a mini-spindle [15]. Electron microscopy analyses indicated that only a small fraction (~4%) of the total microtubules were kinetochore-associated, leading to the proposal that the chromosome—and not just the kinetochore—contributes to microtubule formation.…”
Section: Overlapping Mechanisms Of Microtubule Formationmentioning
confidence: 99%
“…For example, when a microneedle is used to “cut” the spindle, it recovers its bipolar shape [12]. What is even more remarkable is that when two spindles are close enough to interact, they can fuse to form a single spindle of the same size as the original individual spindles [13,14,15]. One might assume that spindle size and shape are somehow intrinsically set by the biochemical components, and therefore such repair and fusion are possible.…”
Section: Introductionmentioning
confidence: 99%